Birds of prey. The complete series [videorecording (DVD)] - Kalogridis, Laeta; Scott, Ashley, 1977-; Meyer, Dina, 1968-; Skarsten, Rachel, 1985-; Moore, Shemar, 1970- (Distributed by Warner Home Video, 2008)
Who will stand up to villains now that a heartbroken Dark Knight has mysteriously vanished? Never fear, New Gothamites, a trio of champions is ready to take wing-- and Helena, the daughter of Batman and Catwoman, is among them. She calls herself Huntress and crime is her prey. Teenaged Dinah is the youngest of the group, learning as she goes and gifted in clairvoyance. And overseeing the awesome threesome's high-tech nerve center is Batgirl. Left wheelchair-bound by The Joker, she has reinvented herself as Oracle, the team's cyber expert.